DEVELOPMENT OF GOOGLE SITES MEDIA AS A CONTEXTUAL AND INTERACTIVE INNOVATION FOR TEACHING AL-QUR’AN AND HADITH - Nuaimah Anatul Maula; Darodjat Darodjat; Zakiyah Zakiyah (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study aimed to develop and evaluate a Google Sites–based learning medium as an innovation for contextual and interactive Al-Qur’an Hadith instruction in a Grade VIII digital-class setting at MTs Negeri 4 Cilacap. The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Needs analysis with 32 students indicated high digital readiness (100% smartphone ownership; 78% frequent internet use; 91% preference for digital learning) and strong demand for video- and audio-supported learning. The product integrated Qur’anic text, murattal audio, instructional videos, interactive quizzes, and online reflection tasks in a single portal. Expert validation (five-point scale) confirmed feasibility, with a content expert score of 4.50/5.00 and a media expert score of 4.00/5.00, followed by minor revisions. A limited pilot trial (n = 10) showed full accessibility and positive usability feedback, and the field implementation (n = 32) yielded an average quiz score of 2,627 points with 80% accuracy and 80.5% mastery. Student responses reached 89.25% (very good). These findings indicate that Google Sites can function as a low-cost, scalable, and pedagogically meaningful platform to support CTL-oriented learning and Qur’anic value internalization in digital madrasah contexts.